2020
DOI: 10.1186/s43014-020-00030-0
|View full text |Cite
|
Sign up to set email alerts
|

Hop-induced formation of ethyl esters in dry-hopped beer

Abstract: Fruity smelling esters play an important role for the aroma of hops and beer and they have been characterized as key aroma compounds in different hop varieties. Studies on the transfer of hop-derived compounds into beer during dry-hopping showed calculated transfer rates of different ethyl esters far above 100%, leading to the assumption that these esters must be newly formed. To investigate this formation, dry-hopping was imitated in water to eliminate the influence of the beer matrix on the formation of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…After days 3‐4, an additional formation of ethyl and methyl esters started (Figure 2A‐D). This phenomenon of a hop‐induced ester formation has been recently described 11 . As the reaction type has not yet been completely clarified, it cannot finally be explained, which external factors caused the differences between the two replicates.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…After days 3‐4, an additional formation of ethyl and methyl esters started (Figure 2A‐D). This phenomenon of a hop‐induced ester formation has been recently described 11 . As the reaction type has not yet been completely clarified, it cannot finally be explained, which external factors caused the differences between the two replicates.…”
Section: Resultsmentioning
confidence: 95%
“…Nevertheless, it was observed that a higher formation rate of methyl esters seems to correlate with a lower rate of ethyl esters (except for propyl 2‐methylbutanoate with a maximal transfer rate of 60% within the first 24 hours, followed by a constant decrease of its concentration; Figure 2E). In a very recent study, it has been reported that the propyl ester is not affected by the hop‐induced ester formation 11 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IBU (International Bitterness Units) are units by which the content of bitter substances in mg/L of beer is expressed by a spectrophotometric determination of the isohumulone concentration. The process should not exceed 120 minutes because beer could acquire an old taste and the color of the wort could increase too much (Brendel et al, 2020). Novotný (2019) states that there are also so-called unconventional hop methods, e. g. mashing hops and cold hops.…”
Section: Basic Raw Materials For Beer Productionmentioning
confidence: 99%